Steroid contraception and the risk of neoplasia : report of a WHO scientific group, meeting held in Geneva from 5 to 9 December 1977 - WHO Scientific Group on Steroid Contraception and the Risk of Neoplasia; World Health Organization (Geneva : World Health Organization, 1978)
Evaluates the design and findings of epidemiological studies focused on the link between the use of steroid contraceptives and cancer in women. Data evaluated cover combined and progestogen-only contraceptives, and estrogens used for non-contraceptive purposes. A brief concluding section considers the relevance of these findings to developing countries.
1. Introduction -- 2. Combination oral contraceptives -- 3. Progestogen-only contraceptives -- 4. Estrogens used for non-contraceptive purpose -- 5. Methodological considerations -- 6. Relevance of existing data from more developed countries to disease risk in less developed countries -- 7. Recommendations -- References
Keywords: Adverse effects; Chemically induced; Steroid; Neoplasia